Private Law, Regulation, and Justice. Issue 5 (September 2016) - Hesselink, Martijn W.
Abstract: This paper critically engages with the European Regulatory Private Law thesis (ERPL). The main strength of ERPL is that it offers an entirely new perspective on European private law. However, as a complete theory of European private law, ERPL is too one‐sided, both from a descriptive and from a normative point of view. With its strong focus on the private law locked up in regulatory silos for specific market sectors, it obscures the reality of the consumer acquis and its transformative force. A fuller picture would include the contours of a loosely coherent system of European private law that is currently emerging. The main pillars of that pragmatic system are (for now) the withdrawal rights, unfair term control, and remedies for nonconformity. Moreover, the contribution of European private law to access justice cannot be the only standard for its evaluation and critique; at least as important are interpersonal justice and democratic legitimacy.